1997
DOI: 10.1152/physrev.1997.77.2.425
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional changes in mitochondria associated with aging

Abstract: This review is devoted to the molecular genetics and bioenergetics of human mitochondria related to the mechanism of aging. Morphological and functional changes of mitochondria associated with age and age-related disease are overviewed with special reference to the changes in enzymes encoded by mitochondrial-inherent genome. The somatically acquired mutations and oxidative damage of the genome, which lead an individual to the fragmentation of mitochondrial DNA, cellular energy crisis, naturally occurring cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(173 citation statements)
references
References 0 publications
3
163
0
7
Order By: Relevance
“…The mitochondrial genome is extremely susceptible to damages from continuous exposure to ROS. These molecules endogenously are produced in mitochondrial respiratory chain and are evidenced to increase the ratio of point mutations in mtDNA [47]. This effect is probably through inhibition of the repair system in mtDNA, detoxification of ROS, or Due to difficulties for obtaining aborted materials, our work was only focused on maternal blood.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial genome is extremely susceptible to damages from continuous exposure to ROS. These molecules endogenously are produced in mitochondrial respiratory chain and are evidenced to increase the ratio of point mutations in mtDNA [47]. This effect is probably through inhibition of the repair system in mtDNA, detoxification of ROS, or Due to difficulties for obtaining aborted materials, our work was only focused on maternal blood.…”
Section: Discussionmentioning
confidence: 99%
“…Since mitochondria did not appear swollen in any age group, this finding indicates that mitochondria increase in size with age. Age-related increases in mitochondrial size have been reported in the rat cerebellum [2] and in human [24] and mouse [28] liver (for review see [18]); however, Herbener [7] found no such changes in mouse heart and liver.…”
Section: Discussionmentioning
confidence: 99%
“…They are often enlarged, sometimes excessively, and thus are called 'giant' mitochondria [54,55]. Mutations of mtDNA and protein alterations steadily increase with age [57,58]. The proportion of normal mitochondria progressively declines, resulting in diminished respiration and lowered ATP production [54,56].…”
Section: Cellular Manifestations Of Ageingmentioning
confidence: 99%
“…Thus, mitochondria represent the primary target of self-produced ROS, probably explaining why these organelles are particularly affected by age. Another probable reason for the pronounced changes of mitochondria in ageing cells follows from the properties of mtDNA, which lacks introns, is almost completely expressed, and has a relatively low repair capacity [57]. Mutations of mtDNA can account for the defective synthesis of 13 respiratory chain proteins, while alterations to other proteins would reflect damage to nDNA.…”
Section: Mechanisms Of Mitochondrial Damagementioning
confidence: 99%